Pengaruh Inovasi Produk, Citra Merek Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Konsumen Pada Bromfiets Cafe Srengat Blitar - Ulhaq, Milza Eluiza; Muttaqien, Zaenul; Evasari, Aprilia Dian (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the influence of product innovation, brand image, and service quality on consumer purchasing decisions at Bromfiets Cafe Srengat Blitar. The research is motivated by the growing competition in the culinary industry, which requires businesses to continuously innovate, strengthen brand image, and improve service quality to retain customers. The research method employed a quantitative associative approach, with data collected through questionnaires distributed to 121 respondents selected using the accidental sampling technique. The data were analyzed using multiple linear regression with the aid of SPSS version 25.0. The results show that product innovation, brand image, and service quality have a positive and significant effect both partially and simultaneously on consumer purchasing decisions. The Adjusted R² value of 0.727 indicates that these three variables explain 72.7% of the variation in purchasing decisions, while the remaining 27.3% is explained by other factors outside the research model. These findings highlight that the synergy between product innovation, brand image, and service quality is the key factor influencing purchasing decisions and sustaining competitive advantage in local culinary businesses.